Five Cases of Congenital Cysts at the Tongue Base - Watanabe, Makiko; Ogahara, Noboru (Pediatric Otorhinolaryngology Japan, 2005)
Introduction: Neonates and Infants with congenital cysts at the tongue base frequently show upper airway obstruction. We report five cases of cysts at the tongue base. Subjects: Five children (three males and two females) who visited our department for a cyst at the tongue base in the period from April 2000 to August 2004. Results: Their chief complaints were stridor, dyspnea, and vomiting. Three children showed their respective symptoms at one month after birth, one at two months and one at three years. We performed laryngoscopic surgery to open the cystic wall in all cases. In two cases, the histopathology of the resected specimen confirmed the diagnosis of a thyroglossal duct cyst. No recurrence has been observed. Conclusion: Laryngoscopy, lateral neck X-ray film, CT, MRI and ultrasonography were especially useful for the diagnosis of this case.